2018
DOI: 10.1002/ece3.4463
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the cover and richness of intertidal macroalgae in remote areas: a case study in the Antarctic Peninsula

Abstract: Antarctica is an iconic region for scientific explorations as it is remote and a critical component of the global climate system. Recent climate change causes a dramatic retreat of ice in Antarctica with associated impacts to its coastal ecosystem. These anthropogenic impacts have a potential to increase habitat availability for Antarctic intertidal assemblages. Assessing the extent and ecological consequences of these changes requires us to develop accurate biotic baselines and quantitative predictive tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous investigations have studied the distribution and relative abundance of lichen, mosses and grasses on the Antarctic Peninsula using low-resolution satellite data (e.g. Haselwimmer & Fretwell 2009, Fretwell et al 2011, Casanovas et al 2015, Kotta et al 2018), while others have studied the spectral signatures of microbial mat communities in non-polar environments (e.g. Andréfouët et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have studied the distribution and relative abundance of lichen, mosses and grasses on the Antarctic Peninsula using low-resolution satellite data (e.g. Haselwimmer & Fretwell 2009, Fretwell et al 2011, Casanovas et al 2015, Kotta et al 2018), while others have studied the spectral signatures of microbial mat communities in non-polar environments (e.g. Andréfouët et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Model performance was evaluated using the cross-validation statistics calculated during model fitting 56 . For more details on the BRT modeling see Kotta et al 57 . Standard errors for the predictions and pointwise standard errors for the partial dependence curves, produced by R package "pdp" 58 , were estimated using bootstrap (100 replications).…”
mentioning
confidence: 99%
“…In the marine environment such studies have generally compared classification results across the two types of imagery (Brodie et al, 2018). In Kotta et al (2018) strong relationship was found between the cover of algae (determined through quadrat data) and reflectance values from satellite imagery. This relationship was specifically for green algae, possibly due to the use of single reflectance bands from satellite imagery.…”
Section: Research Articlementioning
confidence: 99%